2021
DOI: 10.22190/fupes201111056k
|View full text |Cite
|
Sign up to set email alerts
|

The Connection Between the Agility of Adolescent Soccer Players and Their Body Composition

Abstract: The aim of this study is to determine body composition (BC) factors that influence agility among adolescent soccer players (N=66), in U14, U16, U18 soccer teams of the Topola Sport Club. Agility tests (Dribbling test, Illinois test), Inbody 720 instrument measuring the BC, and Oxa Starter infrared timing gate instrument measuring speed the agility were used. Data are processed by the IBM SPSS Statistics 25 software. In addition to descriptive statistics, a correlation matrix analysis, linear regression and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In defenders, the results also indicate a correlation between a96369 and PMM, as well as in a45Lop with BMI, BFkg, BF% and PMM. Agility is one of the most important motor abilities, and such results indicate that agility is significantly affected by muscle mass percentage, BMI, and body fat percentage [33].…”
Section: Discussionmentioning
confidence: 95%
“…In defenders, the results also indicate a correlation between a96369 and PMM, as well as in a45Lop with BMI, BFkg, BF% and PMM. Agility is one of the most important motor abilities, and such results indicate that agility is significantly affected by muscle mass percentage, BMI, and body fat percentage [33].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, a high level of agility is not strongly dependent on acceleration and sprinting speed alone, but also on the ability to coordinate movement, technical skill, anticipate other player’s actions, visually scan the environment, and react to the visual cues of one’s opponents in order to provide a quick and appropriate response [ 1 , 3 , 4 , 5 ]. The anthropometric parameters also play a significant role in the agility results, for example, due to the importance of body dimensions in the results of motor tests, i.e., body height, leg length, or body mass index [ 6 , 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…The importance of body dimensions such as body height or leg length in the results of motor tests determining the components of agility has been demonstrated in numerous studies [ 7 , 12 , 13 ]. Lower body height in shorter players, and at the same time lower COM position, is important for getting better results in CODS and agility tests [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown anthropometric parameters to be related to both CODS and RA (Chaouachi et al, 2009 ; Young et al, 2015b ), due to the importance of body dimensions in the results of motor tests, that is, body height or legs length (Koltai et al, 2021 ). The explanation is, for example, the lower position of the COM, which determines the efficiency of the COD test, and which is lower in the case of shorter players (Young et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%